2017
DOI: 10.1515/acb-2017-0012
|View full text |Cite|
|
Sign up to set email alerts
|

The blood vessels development, morphogenesis and blood circulation are three ontologic groups highly up-regulated in porcine oocytes before in vitro maturation

Abstract: The blood vessels development, morphogenesis and blood circulation are three ontologic groups highly up-regulated in porcine oocytes before in vitro maturation AbstractThe mammalian oocytes undergo significant biochemical and structural modifications during maturation both in vitro and in vivo. These changes involve chromatin reorganization and modification within metabolic status of cytoplasmic organelles. After oocytes' successful maturation the substantially increased storage of RNA was observed. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Considering the biological roles of the most up-and down-regulated genes, it can be concluded that these changes may indicate the increased metabolic and proliferation activity of studied cells in primary in vitro culture. This assumption is consistent with our earlier studies showing that, after long-term culture, the OECs still proliferate and maintain their tube forming properties [10,34].…”
supporting
confidence: 93%
“…Considering the biological roles of the most up-and down-regulated genes, it can be concluded that these changes may indicate the increased metabolic and proliferation activity of studied cells in primary in vitro culture. This assumption is consistent with our earlier studies showing that, after long-term culture, the OECs still proliferate and maintain their tube forming properties [10,34].…”
supporting
confidence: 93%
“…Microarray DNA technology is a useful method to examine changes in gene expression. Analysis of the oocyte transcriptome could be a powerful tool for improving our knowledge about the pathways involved in oocyte development [11]. Microarray technology has enabled the discovery of many ontological groups, closely or loosely associated with oocyte development or CC proliferation and apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, the cells’ morphological composition and metabolic/homeostasis status belong to the main features that describe tissue biology [ 5 , 6 , 7 ]. Although the morphological architecture of oral mucosa is well recognized using several histological methods, the metabolic versus biochemical status of these cells cultured primary in vitro, is not entirely known.…”
Section: Introductionmentioning
confidence: 99%